Inflammatory Effects of Menthol vs. Non-menthol Cigarette Smoke Extract on Human Lung Epithelial Cells: A Double-Hit on TRPM8 by Reactive Oxygen Species and Menthol - Lin, An-Hsuan (Front Physiol, 2017)
Clinical studies suggest that smokers with chronic obstructive pulmonary disease who use menthol cigarettes may display more severe lung inflammation than those who smoke non-menthol cigarette. However, the mechanisms for this difference remain unclear. Menthol is a ligand of transient receptor potential melastatin-8 (TRPM8), a Ca(2+)-permeant channel sensitive to reactive oxygen species (ROS). We previously reported that exposure of human bronchial epithelial cells (HBECs) to non-menthol cigarette smoke extract (Non-M-CSE) triggers a cascade of inflammatory signaling leading to IL-8 induction. In this study, we used this in vitro model to compare the inflammatory effects of menthol cigarette smoke extract (M-CSE) and Non-M-CSE and delineate the mechanisms underlying the differences in their impacts. Compared with Non-M-CSE, M-CSE initially increased a similar level of extracellular ROS, suggesting the equivalent oxidant potency. However, M-CSE subsequently produced more remarkable elevations in intracellular Ca(2+), activation of the mitogen-activated protein kinases (MAPKs)/nuclear factor-κB (NF-κB) signaling, and IL-8 induction. The extracellular ROS responses to both CSE types were totally inhibited by N-acetyl-cysteine (NAC; a ROS scavenger). The intracellular Ca(2+) responses to both CSE types were also totally prevented by NAC, AMTB (a TRPM8 antagonist), or EGTA (an extracellular Ca(2+) chelator). The activation of the MAPK/NF-κB signaling and induction of IL-8 to both CSE types were suppressed to similar levels by NAC, AMTB, or EGTA. These results suggest that, in addition to ROS generated by both CSE types, the menthol in M-CSE may act as another stimulus to further activate TRPM8 and induce the observed responses. We also found that menthol combined with Non-M-CSE induced greater responses of intracellular Ca(2+) and IL-8 compared with Non-M-CSE alone. Moreover, we confirmed the essential role of TRPM8 in these responses to Non-M-CSE or M-CSE and the difference in these responses between the both CSE types using HBECs with TRPM8 knockdown and TRPM8 knockout, and using HEK293 cells transfected with hTRPM8. Thus, compared with exposure to Non-M-CSE, exposure to M-CSE induced greater TRPM8-mediated inflammatory responses in HBECs. These augmented effects may be due to a double-hit on lung epithelial TRPM8 by ROS generated from CSE and the menthol in M-CSE.